INVESTIGATION OF LINGUISTIC FEATURES AS ECOLOGICAL ELEMENTS IN PAKISTANI ENGLISH NEWSPAPERS: A CORPUS-BASED STUDY - Zafar Iqbal Bhatti (PUPIL: International Journal of Teaching, Education and Learning, 2026)
The emergence of ecological discourse has given birth to new approaches and new dynamics of research in language studies. The present study is conducted to understand the linguistic features of environmental elements in English newspapers. Dawn and The Nation were selected as the sample for the present study. Both newspapers are widely read and are loaded with the eco-vocabulary. The study has adopted corpus methodology to conduct the research by selecting 50 different ecological words and presenting them as linguistic features. The study is wide in range, so the study was further delimited to widely use 15 words. AntConc is used as the software to prepare the corpus of both newspapers. Seventy-two articles were found in The Nation, and 85 in The Dawn related to the ecological dynamics. The selected timeline of the study is January 2024 to July 2024. To find out the linguistic features, the study explores metaphors (source domains, target domains), context (character, plot, setting), linguistic features (lexical, syntactic, and discourse), frames, and narrative. The study found that the approach of using ecological discourse in The Dawn is wider in range than in The Nation. The nation covers national and local concerns, while The Dawn widely uses dynamic perspectives.